Human body composition - Wang, Zi Mian; Going, Scott B.; Heymsfield, Steven 1944-; Lohman, Timothy G. 1940- (Champaign, IL Human Kinetics, 2005)
The new edition of Human Body Composition is the most complete text in the burgeoning field of body composition research. The book covers the full range of methods to assess body composition, including dual-energy X-ray absorptiometry, electrical impedance, and imaging techniques. Maintaining the focus of the first edition as a definitive research guide, this resource incorporates updated information on methods and topics of biological importance. This thoroughly revised reference includes new material on: molecular genetics; energy expenditure; body composition as related to various pathological states including cancer, inflammatory diseases, and illnesses associated with HIV; and animal body composition. The information is presented in five logical parts along with an appendix for easy comprehension of the material. Part I presents an introduction to the field and sets the tone for the ensuing chapters. Part II provides an extensive review of the available body composition methods, including measurement cost, safety, and practicality. Part III features reviews on specific body composition components of widespread interest, adipose tissue and skeletal muscle, along with a review of body composition models. Part IV covers the biological influences on body composition such as age, ethnicity, and gender. Part V outlines pathological states related to body composition, including morbidity-mortality links. Human Body Composition, Second Edition, provides a comprehensive account of the science behind human body composition methods. Filled with reliable and accurate information, it is an essential tool and an indispensable reference for exercise science researchers, practitioners, and graduate students who are interested in body composition.
Part I. The Science of Body Composition Research -- Chapter 1. Study of Body Composition: An Overview / Wei Shen, Marie-Pierre St-Onge, ZiMian Wang, and Steven B. Heymsfield ; History ; Body Composition Rules and Models ; Future Directions -- Part II. Body Composition Measurement Methods -- Chapter 2. Hydrodensitometry and Air Displacement Plethysmography / Scott B. Going ; Body Composition Models ; Estimation of Body Volume by Underwater Weighing ; Recommended Procedures for Hydrodensitometry ; Air Displacement Plethysmography ; Summary -- Chapter 3. Hydrometry / Dale A. Schoeller ; Total Body Water ; Intracellular Water and Extracellular Water ; Summary -- Chapter 4. Whole-Body Counting and Neutron Activation Analysis / Kenneth J. Ellis ; Whole-Body Counting ; Neutron Activation Analysis -- Chapter 5. Dual-Energy X-Ray Absorptiometry / Timothy G. Lohman and Zhao Chen ; History and Development of DXA ; Assumptions of DXA and Their Validity ; Applicability of DXA ; Equipment: Hardware ; Equipment: Software ; Measurement Procedures ; Calibration Procedures ; Precision of Total and Regional Composition Estimates ; Accuracy of DXA for the Measurement of Fatness ; Accuracy of DXA Regional Body Composition Assessments ; Estimating Body Composition Changes ; Hydration Status As a Confounder in DXA Body Composition Estimates ; Application of DXA to Pediatric Populations ; DXA Use in Multicomponent Models ; Steps Toward Standardization of DXA ; Recommended Procedure for DXA Measurements ; Summary -- Chapter 6. Bioelectrical Impedance Analysis / Wm. Cameron Chumlea and Shumei S. Sun ; Physical Electrical Properties ; Bioelectrical Properties ; Measuring Impedance ; Impedance History ; Single- and Multiple-Frequency Impedance ; Impedance and Body Composition ; Changes in Body Composition ; Segmental Bioelectrical Impedance ; Impedance and Blood Chemistry ; Summary -- Chapter 7. Computed Tomography and Magnetic Resonance Imaging / Robert Ross and Ian Janssen ; CT Image Acquisition ; MRI Image Acquisition ; CT Image Analysis ; MRI Image Analysis ; Determination of Tissue Volume ; CT Measurement of Skeletal Muscle Tissue Quality ; CT Measurement of Liver Tissue Quality ; MRI Measurement of Skeletal Muscle Tissue Quality ; MRI Measurement of Liver Tissue Quality ; Validity of Tissue Quantity by CT ; Validity of Tissue Quantity by MRI ; Comparison of CT and MRI ; Applications of CT and MRI on Tissue Quantity and Quality ; Future Directions ; Potential of CT and MRI in Large-Scale Studies ; Summary -- Chapter 8. Anthropometry and Ultrasound / Anna Bellisari and Alex F. Roche ; Anthropometry ; Ultrasound ; Summary -- Chapter 9. Pediatric Body Composition Methods / Aviva Sopher, Wei Shen, and Angelo Pietrobelli ; Multicomponent Models ; Hydrodensitometry ; Air Displacement Plethysmography ; Dilution Methods ; Whole-Body Counting ; Electrical Methods ; Dual-Energy X-Ray Absorptiometry ; Imaging Methods ; Anthropometry ; Summary -- Chapter 10. Animal Body Composition Methods / Maria S. Johnson and Tim R. Nagy ; Carcass Analysis ; Total Body Electrical Conductivity (TOBEC) ; Total Body Water by Isotope Dilution ; Dual-Energy X-Ray Absorptiometry (DXA) ; Computed Tomography (CT) ; Magnetic Resonance Spectroscopy (MRS) ; Magnetic Resonance Imaging (MRI) ; Summary -- Chapter 11. Statistical Methods / Shumei S. Sun and Wm. Cameron Chumlea ; Accuracy of Predictive Equations ; Validity of the Response Variable ; Precision of the Predictor Variables ; Relationships Between Predictor Variables and Response Variables ; Statistical Methods ; Size and Nature of the Sample ; Published Predictive Equations ; Summary -- Part III. Body Composition Models and Components -- Chapter 12. Multicomponent Molecular-Level Models of Body Composition Analysis / ZiMian Wang, Wei Shen, Robert T. Withers, and Steven B. Heymsfield ; General Concepts of Molecular-Level Body Composition Methods ; Three-, Four-, and Six-Component Hydrodensitometry Methods ; Four- and Six-Component Neutron Activation Methods ; Six-Component Total Body Carbon Method ; Multicomponent Total Body Protein Method ; Summary -- Chapter 13. Measuring Adiposity and Fat Distribution in Relation to Health / Luiś B. Sardinha and Pedro J. Teixeira ; Total Body Fatness ; Fat Distribution ; Summary -- Chapter 14. Assessing Muscle Mass / Henry C. Lukaski ; Anthropometric Indicators of Muscle Mass ; Muscle Metabolites ; Radiographic Methods ; Nuclear Techniques ; Bioelectrical Impedance Analysis ; High-Frequency Energy Absorption (HFEA) ; Summary -- Chapter 15. Body Composition, Organ Mass, and Resting Energy Expenditure / Dympna Gallagher and Marinos Elia ; Measurement of REE ; Quantifying Specific Organ and Tissue Masses ; Specific Metabolic Rates of Organs and Tissues ; Modeling REE ; REE and Organ Metabolic Rates During the Life Span ; REE: Race and Ethnicity ; REE in Disease ; Ongoing Efforts in the Measurement of Tissue-Specific Metabolic Rates ; Summary -- Part IV. Body Composition and Biological Influences -- Chapter 16. Genetic Influences on Human Body Composition / Peter Katzmarzyk and Claude Bouchard ; Basic Concepts ; Methods ; Genetics and Body Fat Content ; Genetics and Fat Topography ; Genetic Pleiotropy and Body Fat Phenotypes ; Genetics and Skeletal Muscle Phenotypes ; Summary -- Chapter 17. Age / Richard N. Baumgartner ; Fat Mass ; Fat Distribution ; Fat-Free Mass ; Summary -- Chapter 18. Variation in Body Composition Associated With Sex and Ethnicity / Robert M. Malina ; Reference Values ; Total Body Composition ; Adipose Tissue Distribution ; Bone As a Component of Body Composition ; Skeletal Muscle ; Summary -- Chapter 19. Pregnancy / Sally Ann Lederman ; Why Measure Pregnancy Body Composition? ; Measuring Body Composition Changes During Pregnancy ; Advances of the Field -- Chapter 20. Exercise / Daniel P. Williams, Pedro J. Teixeira, and Scott B. Going ; Body Weight ; Whole-Body Fat ; Visceral Adipose Tissue ; Fat-Free Mass, Lean Soft Tissue, and Skeletal Muscle ; Bone ; Summary -- Chapter 21. Hormonal Influences on Human Body Composition / Marie-Pierre St-Onge and Per Bjorntorp ; Hormonal Effects Through the Life Cycle ; Effects of Glucocorticoids ; Interactions Between Hormones ; Effects of Adipocyte-Derived Hormones ; Regulation of Energy Exchange ; Summary -- Part V Body Composition and Pathological States -- Chapter 22. Morbidity and Mortality Associations / Jacob C. Seidell ; Anthropometric Measures in Relation to Morbidity and Mortality: Methodological Issues ; Anthropometry, Body Composition, and Mortality ; Body Composition and Aging: Implications for Morbidity and Mortality ; Effect of Age on the Association Between Weight Change and Health ; Effect of Age on the Association Between Fat Distribution and Health ; Summary -- Chapter 23. Body Composition and Cancer / Zhao Chen ; Body Composition and Cancer Risk ; Body Composition and Cancer Treatment ; Cancer-Related Wasting ; Other Applications of Body Composition Assessments in Cancer Research ; Summary -- Chapter 24. Obesity and Diabetes: Body Composition Determinants of Insulin Resistance / Bret H. Goodpaster and David E. Kelley ; Body Mass Index, Waist Circumference, and IR in Type 2 DM and Obesity ; Fat-Free Mass and IR in Type 2 DM and Obesity ; Abdominal Adiposity: Visceral and Subcutaneous Adipose Tissue in Type 2 DM ; Lower-Extremity Adipose Tissue ; Skeletal Muscle Fat Content ; Hepatic Steatosis and IR in Obesity and Type 2 DM ; Effects of Weight Loss on Body Composition and IR ; Summary -- Chapter 25. Body Composition Studies in People With HIV / Donald P. Kotler and Ellen S. Engelson ; Early Studies (1981-1983) ; Body Composition Assessment ; Cross-Sectional Studies ; Studies of Pathogenic Mechanisms ; Nutritional Status and Clinical Outcomes ; Longitudinal Studies ; Studies of Nutritional Therapies ; HIV-Associated Lipodystrophy ; Pseudotruncal Obesity ; Treatment of Fat Redistribution ; Switch Studies ; Summary -- Chapter 26. Inflammatory Diseases and Body Composition / Ian Janssen and Ronenn Roubenoff ; Influence of Metabolic Imbalances on Body Composition ; Influence of Immune Mediators on Metabolism ; Usefulness of Body Composition As a Measure of Chronic Disease Status ; Inflammatory Diseases and Body Composition in Adults ; Inflammatory Diseases and Body Composition in Children and Adolescents ; Summary -- Appendix: Reference Body Composition Tables -- Abbreviations -- References -- Index
Includes bibliographical references
Keywords: Anthropometry; Human body -- Composition; Human body -- Composition -- Measurement